2021
DOI: 10.1021/acsami.1c17338
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Structure and Properties of Na3.1Zr1.55Si2.3P0.7O11 as a Solid Electrolyte and Its Application in a Seawater Battery

Abstract: The ionic conductivity, bend strength, and electrochemical performance in a seawater battery (SWB) of an Na3.1Zr1.55Si2.3P0.7O11 (vA-NASICON) solid electrolyte were compared to those of Na3Zr2Si2PO12 (H-NASICON). vA-NASICON exhibited three times higher total ionic conductivity (8.6 × 10–4 S/cm) than H-NASICON (2.9 × 10–4 S/cm). This is due to the higher bulk ionic conductivity and lower grain boundary resistance of vA-NASICON. The higher bulk conductivity of vA-NASICON is a result of its higher Na content, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…This can also be confirmed by Raman spectroscopy, the wavelength range of 950-1030 cm −1 corresponds to monoclinic structure (Figure S1, Supporting Information). [24] As previously reported, the monoclinic phase exhibited higher ionic conductivity and lower activation energy (0.26 eV) due to its favorable Na + transport in the 3D channel. [17,25] In addition, it was found that the diffraction peak shifted gradually to a small angle as the content of doped F − increased (Figure 1c).…”
Section: Introductionsupporting
confidence: 59%
“…This can also be confirmed by Raman spectroscopy, the wavelength range of 950-1030 cm −1 corresponds to monoclinic structure (Figure S1, Supporting Information). [24] As previously reported, the monoclinic phase exhibited higher ionic conductivity and lower activation energy (0.26 eV) due to its favorable Na + transport in the 3D channel. [17,25] In addition, it was found that the diffraction peak shifted gradually to a small angle as the content of doped F − increased (Figure 1c).…”
Section: Introductionsupporting
confidence: 59%
“…[90,98] A recent report by Go et al reported that a vA-NASICON (Na 3.1 Zr 1.55 Si 2.3 P 0.7 O 11 ) has even better and more suitable properties compared to the Hongtype NASICON. [99] Due to the changed composition and the microstructure, higher ionic conductivity and a lower grain boundary resistance can be obtained. In addition to the higher bend strength, an improved voltage efficiency and higher power output for use in a seawater battery could be demonstrated in this way.…”
Section: Ceramic Membranesmentioning
confidence: 99%
“…In addition to the higher bend strength, an improved voltage efficiency and higher power output for use in a seawater battery could be demonstrated in this way. [99] NASICON structures are known for their use as materials in sodium-ion batteries, both as electrode material and solid electrolytes. Goodenough and Hing discovered this electrode material and showed the formula Na MMA(XO 4 ), where M and MA represent metals and X are silicon, phosphorus, or sulfur.…”
Section: Ceramic Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of Na super ion conductor (NASICON) as the solid electrolyte and separator of the anode and cathode has been focused on to increase the strength and ionic conductivity. [8] The research on anode active materials that play a role as the storage of sodium ions from seawater has been in-depth conducted. [9][10][11][12] In addition, steady progress of the current collector with electrocatalysts has been simultaneously investigated to reduce overpotentials generated in oxygen evolution reaction and oxygen reduction reaction (OER/ORR) at the cathode.…”
Section: Development Of Prismatic Cells For Rechargeable Seawater Bat...mentioning
confidence: 99%